Effect of metal doping (Me = Zn, Cu, Co, Mn) on the performance of bismuth ferrite as peroxymonosulfate activator for ciprofloxacin removal. (March 2023) - Koo, Pooi-Ling; Choong, Zheng-Yi; He, Chao; Bao, Yueping; Jaafar, Nur Farhana; Oh, Wen-Da
Abstract: In this study, a facile hydrothermal method was employed to prepare Me-doped Bi2 Fe4 O9 (Me = Zn, Cu, Co, and Mn) as peroxymonosulfate (PMS) activator for ciprofloxacin (CIP) degradation. The characteristics of the Me-doped bismuth ferrites were investigated using various characterization instruments including SEM, TEM, FTIR and porosimeter indicating that the Me-doped Bi2 Fe4 O9 with nanosheet-like square orthorhombic structure was successfully obtained. The catalytic activity of various Me-doped Bi2 Fe4 O9 was compared and the results indicated that the Cu-doped Bi2 Fe4 O9 at 0.08 wt.% (denoted as BFCuO-0.08) possessed the greatest catalytic activity ( k app  = 0.085 min −1 ) over other Me-doped Bi2 Fe4 O9 under the same condition. The synergistic interaction between Cu, Fe and oxygen vacancies are the key factors which enhanced the performance of Me-doped Bi2 Fe4 O9 . The effects of catalyst loading, PMS dosage, and pH on CIP degradation were also investigated indicating that the performance increased with increasing catalyst loading, PMS dosage, and pH. Meanwhile, the dominant reactive oxygen species was identified using the chemical scavengers with SO4 ˉ, OH, and 1 O2 playing a major role in CIP degradation. The performance of BFCuO-0.08 deteriorated in real water matrix (tap water, river water and secondary effluent) due to the presence of various water matrix species. Nevertheless, the BFCuO-0.08 catalyst possessed remarkable stability and can be reused for at least four successive cycles with >70% of CIP degradation efficiency indicating that it is a promising catalyst for antibiotics removal. Graphical abstract: Image 1 Highlights: Me-doped Bi2 Fe4 O9 (Me = Zn, Co, Cu and Mn) were prepared via hydrothermal method. Cu-doped Bi2 Fe4 O9 (0.08 wt%) Cu have the highest CIP removal via PMS activation. Synergistic interaction (Cu and Fe) and oxygen vacancies promoted the catalysis. 1 O2, SO4 . ˉ and OH contributed significantly towards CIP degradation. PMS activation and CIP degradation pathways were proposed.